2012
DOI: 10.1097/jto.0b013e31824166a5
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Image-Guided Radiation Therapy for Patients with Limited Volume Metastatic Non-small Cell Lung Cancer

Abstract: HIGRT for oligometastatic NSCLC provides durable LeC and may provide long-term PFS in some patients. Future HIGRT studies should optimize patient selection and integration with systemic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 24 publications
(24 reference statements)
4
63
0
Order By: Relevance
“…Weichselbaum et al introduced this term to indicate that there is an intermediate state of lung cancer between metastatic and local disease. Therefore, we decided to follow the inclusion criteria of Hasselle et al and included all patients with ≤5 extrapulmonary metastases [12].…”
Section: Definition Of "Oligometastatic"mentioning
confidence: 99%
“…Weichselbaum et al introduced this term to indicate that there is an intermediate state of lung cancer between metastatic and local disease. Therefore, we decided to follow the inclusion criteria of Hasselle et al and included all patients with ≤5 extrapulmonary metastases [12].…”
Section: Definition Of "Oligometastatic"mentioning
confidence: 99%
“…23,51 The relatively poor results of RT in comparison with surgery may also be attributed to differences in patient selection. 44 In the surgical literature, the majority of patients have metastases confined to the adrenal or have extra-adrenal OM which have also been aggressively treated; have usually had their primary disease resected; must be technically resectable; and medically operable.…”
Section: Discussionmentioning
confidence: 99%
“…10,23 The objective of this review was to analyze the literature describing aggressive treatment of AM (solitary or as a component of an oligometastatic presentation) secondary to NSCLC.…”
Section: Review Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored radiotherapy for primary tumor sites in patients with advanced lung cancer, and the results suggested that it was able to improve the local control rate, relieve the symptoms, and improve the survival rate. However, this benefit was mainly restricted to patients with good performance status and to those with metastases or single metastasis of limited volume (Nestle et al, 2000;Bezjak et al, 2002;Reinfuss et al, 2011;Hasselle et al, 2012). In addition, long radiotherapy intervals, long-term adverse effects, and the high costs confine the application of radiotherapy as well.…”
Section: Discussionmentioning
confidence: 99%